(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study aims to evaluate Bangalore investors' perceptions of AI-powered stock market platforms. The study's primary objectives are to ascertain respondents' familiarity with AI-based stock trading platforms, identify the factors influencing their adoption, and assess perceived risks associated with these technologies. It examines how investors' opinions of AI platforms connect to their past experiences with AI-based financial instruments in addition to contrasting trust, efficiency, and decision-making accuracy between AI systems and traditional human financial advisors. The study also examines security and privacy issues as well as consumer preferences when utilizing AI-powered trading platforms. The study is based on primary data collected from 100 respondents in Bangalore, 73 of whom were men and 27 of whom were women. The findings indicate an increasing awareness of technological advancements in the stock market, since a significant portion of respondents are either somewhat or very familiar with AI-based trading platforms. Accuracy and transparency were shown to be the most significant factors influencing trust in AI-driven platforms. AI-based systems may be helpful in reducing human prejudice, as most respondents acknowledged that emotional bias affects stock market decisions. Despite the fact that many investors consider AI trading to be moderately to extremely risky, the majority of respondents preferred a hybrid approach that combines both AI systems and human experience, and half of the respondents said they would be willing to rely on AI over traditional financial advisors.